Resuscitating the African giant: Urban renewal and inner city redevelopment initiatives along the ‘Corridors of Freedom’ in downtown Johannesburg - Kotze, Nico. Autor; De Vries, Leani. Autor (IGiPZ PAN, 2019)
After more than two decades of attempting to redevelop the inner city of Johannesburg, it is still perceived by scholars, the popular media and the general public as a crime-ridden area of decay. This paper looks at a public transport system, as well as the redevelopment of parks and the provision of housing in the inner city. The Rea Vaya BRT serves as the ’backbone’ for the redevelopment strategy of the City of Johannesburg’s ’Corridors of Freedom’ which aims to mitigate inequality in the city. This research analyses the success and shortcomings of the BRT system, as well as the redevelopment of inner city parks and the provision of housing for the poor in the inner city and along these development axes. Although large amounts of money have been allocated to the redevelopment of the inner city parks and to tracts of land along these so-called Corridors of Freedom, these parks are still proving to be user-unfriendly owing to a lack of maintenance. Although the redevelopment projects appear to be worthy attempts to improve the inner city of Johannesburg these have as yet not proved themselves to be very effective.
24 cm
Keywords: Johannesburg; urban regeneration; redevelopment; parks; housing; transport